Medication Adherence and its Association with Subjective Well-being among Persons with Schizophrenia - Angshu Lama; Arunjyoti Baruah (Indian Journal of Psychiatric Nursing)
Background: Medication nonadherence has been associated with persistence of psychotic symptoms, relapse, and hospitalization in persons with schizophrenia. Adherence to antipsychotic drug treatment is a key issue for nurses and treatment team members. Aim: The study was conducted with the purpose to assess the medication adherence and its association with subjective well-being among persons with schizophrenia. Method: The study followed a quantitative nonexperimental descriptive design. Participants of this study included 85 persons diagnosed with schizophrenia according to ICD-0 taking treatment at LGB Regional Institute of Mental Health, Tezpur. Data were collected using the self-structured sociodemographic datasheet, The Medication Adherence Rating Scale, and The WHO Subjective Well-Being Inventory. Results: 34.1% patients were not adherent to medication. Significant association was found between the medication adherence and subjective well-being (χ2= 6.58 P < 0.05). Significant association was also found between the medication adherence and factor 8, i.e., inadequate mental mastery factor of subjective well-being of the patient (χ2= 10.82 P < 0.05). Pearson correlation coefficient between the medication adherence and subjective well-being was 0.343, so there was positive correlation between the patient's medication adherence and their subjective well-being. Conclusion: The findings of this study reveal that there is a significant association of adherence with the subjective well-being of the patient and that there is a significant positive correlation present between the medication adherence and subjective well-being. Proper psychoedu and support can help clients to improve their medication adherence.